Correlation between structural and optical properties of 30nm and 60nm lead sulfide nanowires - Wu, Chien; Shi, Jen-Bin; Chen, Chih-Jung; Chen, Yu-Cheng; Wu, Po-Feng; Lin, Jer-Yan (Materials letters, 2007)
PbS nanowires with 30nm and 60nm diameter fabricated under the same condition of electrochemical deposition with sulfuric and oxalic anodic alumina membranes (AAM), respectively, have been successfully prepared in order to study their optical properties in relation to their size. Scanning electron microscopy indicates that the 60nm PbS nanowire arrays have the same shape with the 30nm. X-ray diffraction result shows that 60nm PbS nanowires are crystalline and have a highly (200) preferential orientation like 30nm ones. UV spectrum considers the nanowire size decrease as the absorption peak shifts to the blue. The quantum confinement effects compared between 30nm and 60nm PbS nanowire arrays were observed by the measurements of ultraviolet-visible absorption spectroscopy (UV-vis).